Improvement Of Learning Achievement Of Islamic Religious Education Material Of Faith In The Rasul_Rasul Of Allah With The Small Group Discussion Method In Class XI Is 1 SMA 1 Kepenuhan - Makmur Makmur (Indonesian Journal of Basic Education, 2023)
This Class Action Research aims to determine the increase in PAI learning achievement after the application of the Small Group Discussion learning model to students of class XI IIS 1 SMAN 1 Kepehuhan. The type of research used is classroom action research (PTK) or classroom action research (CAR), namely: practical research carried out to solve factual problems faced by teachers as a scrutiny of learning management activities which is applied to students of class XI IIS 1 SMAN 1 Kepenuhan. with the number of learners 8 students. Instruments used to obtain initial data through students' daily scores, learning achievement data with objective tests carried out at the end of cycle I and cycle II. The results showed that pai learning material has faith in Allah's Apostles with a Small Group Discussion model in class XI IIS 1 students of SMAN 1 Kepenuhan is able to increase student learning achievement. Improvement of learning outcomes in precyclical with an average of 55.00 with the number of completed students as many as 1 student or 12.50% to 50% or 4 students with an average learning outcome of 66.25 and an average in Cycle II of 76.25 with 8 students completed or 100%. The student activity increased from 2 students or 25% to 5 students or 62.50% and 8 students or 100% in the second cycle. This shows that, the learning activities and achievements of students in PAI subjects in class XI IIS 1 SMAN 1 Kepenuhan can be improved through the Small Group Discussion learning model.